Pemanfaatan Kopi Arabika (Coffea arabica) dalam Pembuatan Minuman Yoghurt sebagai Pangan Fungsional - Indira Lanti Kayaputri; Rosalina Ilmi Amalia; Fairuz Khairunnisa (Unpad Press, 2022)
The increase in the number of consumers of coffee drinks encourages variations in fermented beverage products that use coffee as an additive, one of which is yogurt. The addition of Arabica coffee which contains polyphenols are thought to stimulate growth and increase the activity of lactic acid bacteria. The purpose of this study was to determine the right concentration in the manufacture of Arabica coffee yogurt so as to produce good characteristics and fit into the yogurt standard SNI 01-2981-2009 and can increase the growth activity of lactic acid bacteria. The research method used was thedescriptive experimental method with two replications and 4 treatments of added coffee concentration variations (0%, 1%, 2%, and 3%). The addition of 1% Arabica coffee to yogurt was the best treatment with the characteristics of total titratable acidity of 1.10% and total lactic acid bacteria of 8.94 Log CFU/g which has met the requirements of SNI 01-2981-2009, pH 4.15, and total polyphenols of 1.54 mgGAE/100 mL.